Review of voluntary approaches in the European Union: Feasibility study on demonstration of voluntary approaches for industrial environmental management in China - Holger Dalkmann; Daniel Bongardt; Katja Rottmann; Sabine Hutfilter (Wuppertal Institut für Klima, Umwelt, Energie, 2005)
The study Review of voluntary approaches in the European Union has been conducted in the context of the project Feasibility study on demonstration of voluntary approaches for industrial environmental management in China and aims at evaluating the experience with voluntary agreements between industry and public authorities in the European Union. It is part of a comparative study between Europe and China. The study aims at providing a basis for adoption and further development of voluntary agreements in China. Therefore, conceptual information and case studies are presented in order to illustrate the instrument, its chances and risks as well as success factors.
urn:nbn:de:bsz:wup4-opus-23016
Keywords: 650